Performance of lucerne (Medicago sativa) under semi-arid ecosystem of Central Gujarat - KHADDA, B S; LATA, KANAK; KUMAR, RAJ; JADAV, J K; RAI, A K (The Indian Journal of Agricultural Sciences, 2015)
The present study was conducted to popularize the improved green fodder production technology in Panchmahals district of Central Gujarat. Constraints in lucerne (Medicago sativa L.) production were identified through participatory approach. Preferential ranking technique was utilized to identify the constraints faced by the farmers in lucerne production. The results revealed that lack of suitable HYVs, scarcity of irrigation water, weed (Cuscuta spp.) infestation and lack of technical knowledge were found to be the four most important factors responsible for the non-adoption of HYVs of lucerne in Panchmahals district of Gujarat. The yield of green fodder from lucerne in demonstrated variety Anand 2 was 610 q/ha as compared to local check (395 q/ha). The percentage increase in the yield over local check was computed to be 54.43.Results of study on economic analysis of the yield performance revealed that the front line demonstrations (Anand 2) recorded higher gross returns (Rupees 91 500/ha) and net return (Rupees 64 500/ha) with higher benefit cost ratio (3.39) as compared to local check (2.61). Mean difference with respect to farmers’ knowledge level after implementation of frontline demonstrations increased with the tune of 37.20. The impact of frontline demonstrations was also analyzed which had reflected significant improvement in knowledge and satisfaction level on the part of farmers.